Pacific Alliance as Counterpart to MERCOSUR - Skřička, Vojtěch; Čermáková, Klára; Kovanda, Lukáš, 1980-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2015)
This thesis focuses on two integration blocks in Latin America -- the Pacific Alliance and MERCOSUR. The analysis should confirm the hypothesis that the integrated countries converge faster than non-integrated. With use of beta-convergence and sigma-convergence approaches, this hypothesis was rejected for the two Latin American integration groups. It is also supposed that market-led policies should diverge from the protectionist countries in terms of per capita income. However, this hypothesis was not neither confirmed, nor rejected for the observed region and time period. The income growth analysis showed that the Pacific Alliance countries are less dependent on their initial incomes than MERCOSUR members. However, the macroeconomic data exhibit multicollinearity, autocorrelation and unit root generated process. The explanatory coefficients likely lose their statistical significance, when this is controlled for. Therefore, the lower growth dependence in the Pacific Alliance integration on initial income cannot be fully confirmed.
Vedoucí práce: Klára Čermáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses